FAKTOR-FAKTOR PSIKOLOGIS PENENTU NIAT IBU-IBU RUMAH TANGGA DI INDONESIA UNTUK MEMBELI PRODUK TIRUAN/PALSU - Hendrian .; Shine Pintor Siolemba Patir (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
This paper aims to examine housewives self-reported intention to buy counterfeit products by employing the Theory of Planned Behavior (TPB) as the research framework. In total, 600 housewives completed a survey questionnaire measuring their responses to seven constructs in the TPB. Structural equation modeling (SEM) was used as the technique for data analysis with two step approach. The results of this study showed that overall the variables in the TPB model (attitude, subjective norms, perceived control behaviors) were able to explain and predict housewives intention to buy counterfeit products. Attitudes toward behavior have a greater influence on intentions to buy. Additional variables that are included: values were able to explain and predict attitudes toward buying behavior, past behavior was able to explain and predict perceived behavioral control, and social status could explain and predict housewives intention to buy counterfeit products.